Impact of the COVID-19 Pandemic on Health-related Quality of Life in Children with Early Onset Scoliosis: Original Research - Kunes, Jennifer A.; Raman, Divya; Matsumoto, Hiroko; Boby, Afrain; Garg, Sumeet; Pahys, Joshua; Roye, Benjamin; Vitale, Michael G.; Study Group, Pediatric Spine (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Background: Throughout the COVID-19 pandemic, decreases in health-related quality of life (HRQoL) have been observed in adults and children, with isolation, economic disruption, school closures, and health-related anxiety likely contributing. In this study, we evaluated the impact of COVID-19 on self-reported HRQoL of EOS patients and their caregivers using the Early Onset Scoliosis Questionnaire-24 (EOSQ-24). Methods: Patients with EOS and their caregivers enrolled in the Pediatric Spine Study Group (PSSG) registry with EOSQ scores from the year before the COVID-19 pandemic and the first year during COVID-19 were included. Two years of before-COVID-19 baseline EOSQ scores were recorded for each patient. We recorded patient medical demographics, scoliosis etiology, and comorbidities. Results: 618 patients met inclusion criteria (255 male, 363 female). All EOSQ subscores increased significantly from pre-COVID to early-COVID (p < 0.001, p < 0.05, respectively), though the mean difference was well below the proposed EOSQ-24 MCID. There was no evidence of change in Combined HRQoL or impact- and satisfaction-related scores between early COVID to late COVID (p > 0.37). When stratified by etiology, there was no evidence of decrease in the HRQoL combined score or other subscores in any subgroup between pre-COVID and during COVID. Conclusions: Overall, there was no evidence of negative impact on HRQoL by the COVID-19 pandemic for children with EOS or their caregivers. In the future, protective factors contributing to the resilience of this population may be explored further.